Efficacy of Cytoflavin in Therapy of Encephalophathy in Patients with Neuroinfection - V. A. Isakov; A. L. Kovalenko; O. V. Martynova; V. V. Turkin; V. I. Makarov (Антибиотики и Химиотерапия, 2020)
The use of cytoflavin solution in complex therapy of patients with neuroinfection was studied. It showed a favourable effect on the disease clinical process, evident from less pronounced intoxication and meningeal signs by the 11th day of the treatment and improvement of the liquorological picture. The cytoflavin efficacy was also confirmed by normalization of the brain bioelectric activity evident from the electroencephalograms and by reduction of the level of antioxidants, such as metalloproteids and superoxidodismutase, that was in favour of the drug antiinflammatory and antioxidant effects. The use of cytoflavin tablets during in early convalescence period promoted earlier recovery of the intellectual and mnestic reactions. On the whole, the use of cytoflavin promoted favourable process and outcomes of neuroinfections and could be recommended for the use during the acute state and re habilitation of the patients.